2020
DOI: 10.1186/s43094-020-00043-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of electrospun keratin/coenzyme Q10/poly vinyl alcohol nanofibrous scaffold containing mupirocin as potential dressing for infected wounds

Abstract: Background: Nanostructured wound dressings produced by electrospinning biocompatible polymers possess great potential because they resemble the natural extracellular matrix and support cell adhesion, proliferation, and differentiation. This study seeks to fabricate mupirocin, keratin, and coenzyme Q10 (Co Q10)-loaded PVA electrospun scaffolds intended for wound healing application and to characterize their morphology, physical properties, antibacterial activity, and biocompatibility. Polyvinyl alcohol (PVA) (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…This potential dressing for infected wounds was effective in preventing the proliferation of microorganism. Encapsulation of CoQ10 in nanoliposomes has also been shown to enhance CoQ10 activity by accelerating wound healing process after tooth extraction [24,25]. A reduction in inflammatory reaction and increase in collagen deposition following surgical procedure, were previously obtained in animals when CoQ10 was applied in a form of ointment resulting.…”
Section: Extracellular Matrix Targeted For Chronic Woundmentioning
confidence: 96%
See 1 more Smart Citation
“…This potential dressing for infected wounds was effective in preventing the proliferation of microorganism. Encapsulation of CoQ10 in nanoliposomes has also been shown to enhance CoQ10 activity by accelerating wound healing process after tooth extraction [24,25]. A reduction in inflammatory reaction and increase in collagen deposition following surgical procedure, were previously obtained in animals when CoQ10 was applied in a form of ointment resulting.…”
Section: Extracellular Matrix Targeted For Chronic Woundmentioning
confidence: 96%
“…To accelerate healing processes and decrease the complication occurrence various agents, growth factors, natural and synthetic antioxidants (coenzyme Q10-CoQ10), are applied. Amajuoyi et al incorporated natural ECM matrix co-enzyme Q10 and keratin in electrospun keratin/Co Enzyme Q10/Poly vinyl alcohol nanofibrous scaffold [24]. This potential dressing for infected wounds was effective in preventing the proliferation of microorganism.…”
Section: Extracellular Matrix Targeted For Chronic Woundmentioning
confidence: 99%
“…The study of FTIR spectrum for ZM gum is shown in Fig. 6, and it shows a typical absorption band at 3435 cm − 1 which shows the presence of an OH group which is hydrogen-bonded [32]. The bands at 292 cm − 1 shows typical polysaccharide sugars, arabinose, rhamnose, and galactose and shows aldehyde C-H stretch and alkane C-H stretch.…”
Section: Ftir Analysismentioning
confidence: 99%
“…Nanofibers are excellent, three-dimensional, bioengineered therapeutic materials for the treatment of acute and chronic wounds and burns. These are mainly used as dress-ing material due to their structural and functional resemblance to the fibrillar structure of the native extracellular matrix (ECM), wound healing stimulation, biocompatibility, biodegradability leading to support cell adhesion, proliferation, and differentiation [62,87]. Nanofibers also protect the wound from external environmental contamination and adsorb the wound exudates, and their porous nature permeates oxygen, moisture, and eliminates the metabolic waste [88,89].…”
Section: Nanofibersmentioning
confidence: 99%